Austrian Theorists of Central European Integration - El Beheiri , Nadja; Fenzl , Annemarie; Ziegerhofer, Anita (Great Theorists of Central European Integration, 2023)
The figures discussed in this chapter were forward-looking thinkers who were able to adapt to the needs of their times. All of them in one way or another were steeped in the Christian tradition and can be characterised as the forefathers of a United Europe. They were able to set aside their own preferences when a broader ideal required it. Ignaz Seipel was able to negotiate with representatives of the socialist party; although he personally preferred the state form of Monarchy, he played a decisive role in the enactment of the constitution of the Republic of Austria. In the context of his time, he can be considered extraordinarily open minded, not only concerning his political agreements but also, for instance, his friendship with Hildegard Burjan. Richard Coudenhove-Kalergi was an early visionary of European unification in the face of non-European world powers. He saw Pan-America, East Asia, the Russian Empire, the British Empire, and Europe as the five planetary force fields that made up the world. The pathway to strike a balance in this system would have been the founding of the United States of Europe. In 1925, he founded the ‘Paneuropa Union’ with its headquarters in the Vienna Hofburg and with the support of the Ignaz Seipel. The situation in Europe changed significantly after World War II, and Coudenhove- Kalergi adapted his programme to the new geopolitical situation. Until the end of his life, he struggled for the unification of Europe as a guarantee for peace. Otto von Habsburg, son of the last emperor of the Monarchy, can be considered one of the most outstanding supporters of a United Europe. He realised his political activity as successor of Coudenhove-Kalergi as President of the Paneuropen movement and from 1979 as a deputy to the European Parliament. He based his idea of European unification on the principles of democracy, federalism, subsidiarity, and solidarity. Cardinal Franz König advocated for the development of understanding between diverse people and religions. He believed that a United Europe must include both the Eastern and western halves of the continent and should be implemented to uphold peace. He was convinced that promoting Christian unity played a significant role in the progress of this unification and played a significant role in bridging the gap between Eastern and Western Europeans during the Iron Curtain era. Erhard Busek commendably combined his engagement as a local and federal politician with his commitment to the countries of Eastern Europe. In Busek’s view, the Danube should serve as a second river of unification after the Rhine. He further believed that economic cooperation, education, and intensive collaboration should play a preeminent role in the unification process. Busek served as a representative of Austria in the process of the enlargement of the European Union. He also held the position of chairman of the Institute for the ‘Danube Region and Central Europe’.KEYWORDS: European federation, social, state, Pan-European movement, collapse of the Austro-Hungarian Monarchy, nations beyond the Iron Curtain, European federation, enlargement of the European